How to do things with international law - Hurd, Ian (Princeton, New Jersey Princeton University Press, 2017)
"The description for this book, How to Do Things with International Law, will be forthcoming. "--Provided by publisher.
Rule of law, domestic, and international -- How to do things with international law -- The permissive power of the ban on war -- The rule of no-law : drones, nukes, and the Horror Vacui --Torture : legitimacy and legality -- The empire of international legalism.
Includes bibliographical references (pages 139-176) and index.
Keywords: International law; Rule of law